Water saving and economic impacts of land leveling: the case study of cotton production in Tajikistan - Abdullaev, Iskandar; Ul-Hassan, Mehmood; Jumaboev, Kahramon (2007)
Water conservation is essential to prevent salinity and land degradation in Central Asia. Therefore, field-testing and evaluation of water conservation methods, i.e. laser land leveling in new farming systems of Central Asia is important task. This in mind the International Water Management Institute (IWMI) and its regional partner on IWRM FV (IWRM FV project - Integrated Water Resources Management in Ferghana Valley project is funded by Swiss Development Cooperation (SDC) and conducted jointly with IWMI and Scientific Information Center of Interstate Coordination Water Commission (SIC ICWC) in the Ferghana Valley of Central Asia) project SIC ICWC have conducted 3 year study of impacts of the Laser leveled land leveling on water use, productivity and crop yields in northern Tajikistan. The major research question was laser land leveling an effective water saving tool in the new context of land use and ownership on smaller private plots. Can farmers afford the costs of laser land leveling and how economically viable is it? These research questions were studied in 5 ha laser leveled and neighboring non-leveled (control) fields for 2004-2006. The results showed that laser land leveling can reduce the water application rate in 2004 by 593 M3/ha, in 2005 by 1509 M3/ha and in 2006 by 333 M3/ha in comparison with the unleveled field, located in the similar agro-ecological conditions. The deep percolation was 8% lower and run off 24% less than in non-leveled field. The average annual net income from the laser field was 22% higher than that from the control field. The gross margin from the laser-leveled field were 16. 88 and 171% higher compared to that from the control field for 2004, 2005 and 2006, and on average was 92% higher. In spite of these positive results, there are hindrances on wide application of laser land leveling in Tajikistan. These are absence of initial capital of farmers and scattered land location.